1985
DOI: 10.1007/bf00375374
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Qa-1 determinants defined by antisera and by cytotoxic T lymphocytes

Abstract: Cytotoxic T lymphocytes (CTL) activated in H-2 identical, Qa-1 disparate mixed leukocyte cultures recognize H-2-nonrestricted target antigens indistinguishable by strain or tissue distribution from serologically defined Qa-1 antigens. Cloned Qa-1-specific CTL define determinants encoded by four Qa-1 genotypes; we used anti-Qa-1 sera in antibody blocking experiments to determine if these determinants reside on molecules recognized by Qa-1-specific antibodies. Antisera containing Qa-1.1-specific and TL-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Fig. 1 a shows that unprimed B6' mice (which are Qa-1 = [40]) generate very weak CTL responses to B6 (which are Qa-lb), and mice primed in vivo with B6 cells do no better ( Fig. 1 b).…”
Section: A Hapten-carrier System For Cytotoxic T Cellsmentioning
confidence: 99%
“…Fig. 1 a shows that unprimed B6' mice (which are Qa-1 = [40]) generate very weak CTL responses to B6 (which are Qa-lb), and mice primed in vivo with B6 cells do no better ( Fig. 1 b).…”
Section: A Hapten-carrier System For Cytotoxic T Cellsmentioning
confidence: 99%
“…Peptides were purchased from Genemed Synthesis. Flow cytometry analyses of CTL lines was performed as previously described 19 . using anti-CD4 antibody GK1.4 (PharMingen) and anti-CD8α antibody YTS169.4 (kindly provided by Dr. James Forman,) The CTL were CD8 + and CD4 − , as expected.…”
Section: Methodsmentioning
confidence: 85%
“…Using specific strain combinations as described, CTL were generated in secondary MLC as described 19 . Briefly, 5 × 10 6 responder and 5 × 10 6 irradiated (3000Rad) stimulator spleen cells were incubated for 6–7 d in RPMI 1640 supplemented with 7–10% fetal bovine serum, 1% L-glutamine and 50 ng/mL 2-mercaptoethanol at 37°C in 7% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The protein product in the Qa-1' strains is denoted as Qa-1.1, and that in Qa-111 strains as Qa-1.2. The Qa-1 molecules from Qa-1c and Qa-ld strains are very similar to Qa-1.2 as shown by serological, biochemical, and CTL analyses (12)(13)(14)(15)(16).…”
mentioning
confidence: 77%
“…Subsequent biochemical studies revealed Qa-1 antigens to have structural properties characteristic of class I antigens, i.e., cell surface glycoproteins with molecular weight of -48,000 and associated with 02-microglobulin (9)(10)(11) . Four alleles (a,b,c,d) have been defined for the Qa-1 locus by CTL reactions (12)(13)(14)(15). The protein product in the Qa-1' strains is denoted as Qa-1.1, and that in Qa-111 strains as Qa-1.2.…”
mentioning
confidence: 99%